Film file holder with built-in adsorption material
By a composition adsorption material built -in molecular sieve and BA (OH) 2 in the film archives, the problem of prone to acetate syndrome in the preservation process of acetate cellulose ester film is solved. save.
Patent Information
- Application Number
- CN202310209777.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-03-07
AI Technical Summary
Cellulose acetate films are prone to acetate syndrome during storage, resulting in damage to the physical and chemical properties and sound quality of the film, and the commonly used tinplate boxes accelerate this process in a sealed environment.
Design a film archival equipment with built-in adsorption material composed of molecular sieve and Ba(OH)2. Through its excellent acid absorption and moisturizing properties, it can maintain appropriate humidity and inhibit the impact of free acid on the film.
It can effectively prevent the occurrence of acetic acid syndrome, delay film aging, keep the humidity and acidity of the film storage environment within the optimal range, and ensure the long-term preservation of the film and the integrity of the image information.
Smart Images

Figure CN116020407B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cultural relics protection, and in particular relates to a film archive device with built-in adsorption material. Background Art
[0002] Photographic film, as a carrier of artistic information and archives, is an extremely valuable modern cultural heritage. Cellulose acetate film was widely used in the production of motion picture films from the 1940s to the late 1990s, and its quantity accounted for a considerable proportion of various image archives. In 1985, it was discovered that the film base of cellulose acetate film would hydrolyze to produce "acetic acid syndrome", which is a common phenomenon in archives around the world. After the occurrence of acetic acid syndrome, the physical and chemical properties and sound quality of the film will be affected to varying degrees. Macroscopically, it is mainly manifested in the release of acetic acid gas from the film, the surface is covered with crystals, it is distorted, the image layer liquefies and falls off, the entire film is bonded into blocks, the film is severely acidified and brittle, and it cannot be opened.
[0003] The internal cause of acetic acid syndrome is mainly caused by the hydrolysis reaction of cellulose triacetate, the film base material. From the perspective of the molecular reaction process, water molecules attack the carbon atom of the ester group on the six-membered ring, the carbon-oxygen double bond opens, and a molecule of acetic acid is removed. The carbonyl group of the ester group becomes a hydroxyl group, and the molecule changes from hydrophobic to hydrophilic. Therefore, the decay of cellulose acetate film is not only affected by the material it is made of, the temperature and humidity of the storage environment, but also by the archive box that is in close contact with it, which is an important factor affecting its storage life. Tinplate boxes are commonly used as collection equipment during the period when cellulose acetate film was widely used. Iron archive boxes are widely used as packaging materials for film archives because of their high physical strength and good sealing. However, its disadvantage is that the acetic acid gas released by the cellulose acetate film stored inside is gradually enriched in the sealed space, causing the self-catalytic degradation reaction of the film base material, accelerating the occurrence of acetic acid syndrome, and causing serious liquefaction of film bonding. Summary of the invention
[0004] The purpose of the present invention is to provide a film archive device with built-in adsorption material for preventing the occurrence of acetic acid syndrome, aiming at the root cause of the occurrence of acetic acid syndrome in film archives.
[0005] To achieve the above purpose, the built-in adsorption material of the film archive holder used in the present invention is a combination of molecular sieve and Ba(OH)2, wherein the combined mass ratio of molecular sieve to Ba(OH)2 is 1:0.3 to 1:3.
[0006] The above-mentioned adsorption material preferably has a combined mass ratio of molecular sieve and Ba(OH)2 of 1:1 to 1:2.
[0007] Furthermore, the molecular sieve and Ba(OH)2 are placed in non-woven bags respectively and placed at the bottom of the film file container.
[0008] More preferably, the above-mentioned adsorbent material is 50-100 g / 0.1 m 3 Placed at the bottom of the film file holder.
[0009] The beneficial effects of the present invention are as follows:
[0010] 1. The present invention uses tasteless, non-toxic, large specific surface area molecular sieve and Ba(OH)2 as adsorption materials. The composite material has excellent acid absorption and moisturizing effects, and can maintain the humidity at the most suitable humidity of 50%±5% in the storage environment of cellulose acetate film;
[0011] 2. The adsorption material of the present invention can effectively inhibit the autocatalytic effect of free acid and water molecules on the film matrix, prevent further aging of the film, delay the occurrence of acetic acid syndrome, and realize the effective storage of cellulose acetate film. It has strong operability and does not affect the image information recorded on the film.
[0012] 3. The use of the adsorption material of the present invention can enable the film to be stored at room temperature, achieving a good preventive protection effect, reducing the cost of high energy consumption in controlling temperature and humidity in the conventional film collection environment, being environmentally friendly and low-carbon, and having important significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a photograph of the film in Example 1 without any adsorbent material placed thereon and placed at 45°C for 75 days.
[0014] Figure 2 This is a photograph of the film on which the adsorbent material was placed in Example 1 and left at 45° C. for 75 days.
[0015] Figure 3 This is a photograph of the film in Example 2 without any adsorbent material placed thereon and placed at 45°C for 75 days.
[0016] Figure 4 This is a photograph of the film with the adsorbent material placed in Example 2 left at 45°C for 75 days. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0018] Cellulose acetate film is an important component of photosensitive image archives. The decay of cellulose acetate film is not only affected by its own materials, but also by the temperature and humidity of the storage environment, which are important factors affecting its storage life. In particular, the humidity and acidity of the microenvironment in the equipment that is in close contact with it are the main factors affecting the development of acetic acid syndrome. The present invention selects domestic cellulose acetate film produced in the 1980s as the research object, and screens and optimizes the acid-absorbing material built into the film collection box. The specific test is as follows:
[0019] 1. Study on the adsorption performance of a single adsorption material built into film archive holders
[0020] Single molecular sieve, CaO, Ca(OH)2, MgO, Ba(OH)2, silica gel and activated carbon were used as built-in adsorption materials in film collection boxes. The adsorption performance of the adsorption materials for acetic acid and the effect of maintaining environmental humidity were investigated after being placed for different time periods. The results are shown in Tables 1-2.
[0021] Table 1 Measured values of adsorption of acetic acid by different adsorbent materials
[0022]
[0023] The experimental results in Table 1 show that single molecular sieve, CaO, Ca(OH)2, MgO, Ba(OH)2, silica gel, and activated carbon all have a certain adsorption effect on acetic acid, among which CaO, Ca(OH)2, MgO, and silica gel have a more obvious adsorption effect on acetic acid, and after 12 hours, the absorption of acetic acid in the environment is basically completed. The molecular sieve and activated carbon have a slower adsorption rate for acetic acid, but the adsorption is basically complete after 70 hours.
[0024] Table 2 Determination of hygroscopicity of different adsorbent materials
[0025]
[0026] As can be seen from Table 2, while single CaO, Ca(OH)2, MgO, and silica gel adsorb acetic acid well, they also adsorb moisture in the environment. After 5.5 hours, the humidity in the environment gradually decreases. According to the most suitable humidity of 50%±5% in the storage environment of cellulose acetate film, although CaO, Ca(OH)2, MgO, and silica gel have a more obvious adsorption effect on acetic acid, their environmental humidity is poorly maintained and are not suitable as built-in adsorption materials for film archives. After 5.5 hours of adsorption by molecular sieve, Ba(OH)2, and activated carbon, the environmental humidity tends to be stable, and they can be considered as built-in adsorption materials for film archives.
[0027] Combining the experimental results in Table 1 and Table 2, it can be seen that although single CaO, Ca(OH)2, MgO, and silica gel have good adsorption effects on acetic acid, their environmental humidity maintenance is poor, and they are not suitable as built-in adsorption materials for cellulose acetate film equipment; although single molecular sieve and activated carbon have slow adsorption rates on acetic acid, their environmental humidity maintenance effects are relatively stable; Ba(OH)2's acid absorption and moisturizing properties are superior to other adsorption materials. Therefore, Ba(OH)2, activated carbon, and molecular sieves are further used as built-in adsorption materials for equipment to examine their effects on film performance.
[0028] 2. Study on the influence of built-in adsorption materials of film archives on film performance
[0029] Single activated carbon, molecular sieve, Ba(OH)2 and their compound in a mass ratio of 1:1 were used as built-in adsorption materials in film collection boxes. The effects of the adsorption materials on the film performance after being placed at different temperatures for 70 days were investigated. At the same time, a blank test was performed. The results are shown in Tables 3 to 7 (each value is the average of 10 tests).
[0030] (1) Changes in the hydrophilicity of the emulsion layer
[0031] Table 3 Test results of contact angle of different adsorption materials on film emulsion layer
[0032]
[0033] The experimental results in Table 3 show that the initial contact angle of the blank sample film is 82.6°. As the temperature increases, the contact angle gradually decreases. When the temperature increases to 65°C, the contact angle is 45.5°, indicating that the wettability of the imaging layer surface to water is enhanced, mainly because the acetic acid released by the degradation of the film base material triacetate cellulose causes the gelatin in the imaging layer to degrade. As the gelatin degrades, the melting point of the water-soluble emulsion decreases, and the degraded gelatin emulsion layer will immediately dissolve in water or acidic or alkaline solutions. When a single adsorbent material, activated carbon, molecular sieve, and Ba(OH)2, is placed in the film collection box, after the temperature increases to 45°C, although the decrease in its contact angle is smaller than that of the blank sample, after the temperature increases to 55°C, its contact angle decreases significantly. When the mass ratio of activated carbon: molecular sieve = 1:1, activated carbon: Ba(OH)2 = 1:1 is used as a composite adsorption material, as the temperature increases to 45°C, although the contact angle decreases less than that of a single adsorption material, the contact angle still decreases more when the temperature increases to 55°C. When the mass ratio of molecular sieve: Ba(OH)2 = 1:1 is used as a composite adsorption material, the contact angle remains good as the temperature increases, and even when the temperature increases to 65°C, the contact angle is still 80.5°C.
[0034] (2) Changes in the glossiness of the emulsion layer
[0035] Table 4 Test results of glossiness of film emulsion layer by different adsorption materials
[0036]
[0037] From the test results in Table 4, it can be seen that the initial glossiness of the blank sample film emulsion layer is 94.2. When the temperature increases to 45°C, the glossiness begins to decrease. When the temperature increases to 65°C, the glossiness drops sharply to 38.2, indicating that the degradation and liquefaction of gelatin in the image layer will cause the surface to be uneven, making the reflectivity worse and destroying the image information carried. Film degradation will cause the emulsion to flow and lose the coating. When a single adsorbent material, activated carbon, molecular sieve, and Ba(OH)2, is placed in the film collection box, after the temperature increases to 45°C, the glossiness decreases less than that of the blank sample, but after the temperature increases to 55°C, the glossiness begins to decrease significantly. When a composite adsorbent material with a mass ratio of activated carbon: molecular sieve = 1:1 and activated carbon: Ba(OH)2 = 1:1 is used, although the glossiness decreases less than that of a single adsorbent material, as the temperature increases to 55°C, the glossiness also begins to decrease significantly. When a composite adsorption material with a mass ratio of molecular sieve:Ba(OH)2=1:1 is used, the glossiness is maintained well as the temperature increases. When the temperature is 65°C, the glossiness is still 90.1°C.
[0038] (3) Changes in film acidity
[0039] Table 5 Effect of different adsorption materials on film pH
[0040]
[0041] The results in Table 5 show that the initial pH of the blank sample film is 5.80. As the temperature increases, its pH gradually decreases. When the temperature increases to 65°C, the pH decreases to 3.80, which may be related to the deacetylation of cellulose acetate to release acetic acid. When the single adsorbent materials activated carbon, molecular sieve, and Ba(OH)2 are placed in the film collection box, after the temperature increases to 45°C, the pH decrease is smaller than that of the blank sample, but after the temperature increases to 55°C, the pH begins to decrease significantly. When the composite adsorbent material with a mass ratio of activated carbon: molecular sieve = 1:1 and activated carbon: Ba(OH)2 = 1:1 is used, the pH change with the increase of temperature is not much different from that of the single adsorbent material. When the composite adsorbent material with a mass ratio of molecular sieve: Ba(OH)2 = 1:1 is used, the pH is well maintained with the increase of temperature, and the pH is 5.72 at a temperature of 65°C.
[0042] (4) Changes in film mechanical strength
[0043] Table 6 Effect of different adsorption materials on film folding endurance (double)
[0044]
[0045] Table 7 Effect of different adsorption materials on film tensile strength (kN / m)
[0046]
[0047]
[0048] From the data in Table 6 and Table 7, it can be seen that the folding resistance and tensile strength of the blank sample are 32 and 14.6 kN / m, respectively. With the increase of temperature, the folding resistance and tensile strength decrease significantly. When the temperature increases to 65°C, the folding resistance and tensile strength are 7 and 3.8 kN / m, respectively, which decrease by 78% and 73.9%, respectively. This is because the increase in temperature accelerates the breakage of the 1,4-glycosidic bond of the film-based cellulose ester, which is manifested as a decrease in folding resistance and tensile strength on a macro scale. When a single adsorption material, activated carbon, molecular sieve, and Ba(OH)2, is placed in the film collection box, its folding resistance and tensile strength begin to decrease after the temperature increases to 45°C, and the decrease is smaller than that of the blank sample, but when the temperature increases to 65°C, the folding resistance and tensile strength also decrease greatly. When using a composite adsorption material with a mass ratio of activated carbon: molecular sieve = 1:1, activated carbon: Ba(OH)2 = 1:1, as the temperature increases to 55°C, the decrease in folding resistance and tensile strength is not much different from that of a single adsorption material. When using a composite adsorption material with a mass ratio of molecular sieve: Ba(OH)2 = 1:1, as the temperature increases, the folding resistance and tensile strength are maintained well. At a temperature of 65°C, the folding resistance and tensile strength retention rates are 87.5% and 97.3%, respectively.
[0049] Based on the above data, it can be seen that when activated carbon, Ba(OH)2, and molecular sieve are placed in the film collection box alone, although the acid absorption and moisture retention properties meet the use requirements, when the temperature increases to 45°C, the performance parameters of the built-in film begin to decline significantly; when activated carbon and molecular sieve or Ba(OH)2 are compounded in a mass ratio of 1:1 as an adsorption material, the retention of various film properties is better than that of a single adsorption material, but when the temperature increases to 65°C, the performance of the film decreases significantly; only when a compound adsorption material of molecular sieve:Ba(OH)2=1:1 is placed in the film collection box, the hydrophilicity, glossiness, acidity and mechanical properties of the film emulsion layer are well maintained. This shows that compounding molecular sieve and Ba(OH)2 as a built-in adsorption material for film archives is beneficial to the durable preservation of films.
[0050] 3. Effect of the ratio of molecular sieve and Ba(OH)2 on film performance
[0051] The film samples were placed in film collection boxes with molecular sieve and Ba(OH)2 mass ratios of 1:0.3, 1:0.5, 1:1, 1:1.3, 1:1.5, and 1:2, respectively, and placed at 55°C for 75 days. The film properties were tested, and the results are shown in Table 8. A blank control experiment was also performed.
[0052] Table 8 Effect of the ratio of molecular sieve to Ba(OH)2 on film properties
[0053]
[0054] From the data in Table 8, it can be seen that the contact angle of the film emulsion layer, the glossiness of the film emulsion layer, the pH value of the film, the folding endurance (double), and the tensile strength (kN / m) of the blank sample without adsorption material are lower than those of the sample with adsorption material, indicating that the adsorption material is beneficial to the durable preservation of the film. When the ratio of molecular sieve to Ba(OH)2 increases from 1:0.3 to 1:3, its various performance parameters show a trend of increasing first and then decreasing, among which when the mass ratio of molecular sieve to Ba(OH)2 is 1:1 to 1:2, the various performances are optimal.
[0055] Example 1
[0056] Place the film sample in the film collection box and cut it every 0.1m 3 Place 50g of adsorption material, put molecular sieve and Ba(OH)2 in a non-woven bag at a mass ratio of 1:1, place it at the bottom of the film collection box, seal the film collection box, and place it at 45℃ for 75 days. Take out the film and test its various properties. At the same time, a comparative test was conducted without placing adsorption material. The results are shown in Table 9 and Figure 1 , Figure 2 .
[0057] Table 9
[0058]
[0059] From Table 9 and Figure 1 , Figure 2 It can be seen that compared with the film without adsorbent materials, the appearance of the film after placing the adsorbent materials remains intact without obvious deformation, and the contact angle of the film emulsion layer, the gloss of the film emulsion layer, the film pH, the film folding endurance, and the film tensile strength are better than those of the film without adsorbent materials, indicating that placing adsorbent materials plays an important role in the preventive protection of films.
[0060] Example 2
[0061] Place the film sample in the film collection box and cut it every 0.1m 3Place 80g of adsorption material, put molecular sieve and Ba(OH)2 in a non-woven bag at a mass ratio of 1:2, place it at the bottom of the film collection box, seal the film collection box, and place it at 45℃ for 75 days. Take out the film and test its various properties. At the same time, a comparative test was conducted without placing adsorption material. The results are shown in Table 10 and Figure 3 , Figure 4 .
[0062] Table 10
[0063]
[0064] From Table 10 and Figure 3 , Figure 4 It can be seen that compared with the film without adsorption material, the appearance of the film after the adsorption material is placed remains intact without obvious deformation, and the contact angle of the film emulsion layer, the glossiness of the film emulsion layer, the pH value of the film, the folding resistance of the film, and the tensile strength of the film are better than those without adsorption material, indicating that the placement of adsorption material plays an important role in the preventive protection of the film. 3 Compared with placing 50g of adsorbent material, increasing the adsorbent material to 0.1m 3 By placing 80g of adsorbent material, its preventive protection effect increases.
Claims
1. A film file holder with built-in adsorption material, characterized in that: The adsorption material is a combination of molecular sieve and Ba(OH)2, wherein the combined mass ratio of molecular sieve to Ba(OH)2 is 1:0.3 to 1:3; The molecular sieve and Ba(OH)2 are placed in non-woven bags respectively and placed at the bottom of the film file holder; The adsorption material is 50-100 g / 0.1 m 3 Placed at the bottom of the film file holder.
2. The film file holder with built-in adsorption material according to claim 1, characterized in that: The combined mass ratio of the molecular sieve and Ba(OH)2 is 1:1 to 1:2.